PARTISIPASI MASYARAKAT DALAM PROGRAM PENGELOLAAN HUTAN LINDUNG WOSI RENDANI (Participation of Communities in the Wosi Rendani Protected Forest Management) - Anton Silas Sinery; Jacob Manusawai (Jurnal Manusia dan Lingkungan, 2016)
ABSTRAKPartisipasi masyarakat dalam pengelolaan program merupakan hal mendasar yang menentukan keberhasilan penyelenggaraan program. Dalam perspektif konservasi sumber daya alam, partisipasi merupakan prinsip dasar yang menentukan keberhasilan pencapaian program. Tujuan penelitian adalah untuk mengetahui fungsi, intensitas dan tingkat partisipasi masyarakat dalam program pengelolaan hutan lindung Wosi Rendani. Fungsi partisipasi masyarakat dalam pengelolaan kawasan hutan lindung Wosi Rendani tertinggi pada kampung Kentekstar (60,0%), diikuti Ipingoisi (31,11%), Soribo (28,57%) dan Tanah Merah Indah (27,27%) dengan frekuensi 41 responden (34,75%). Konsentrasi responden pada fungsi partisipasi distribusi dengan frekuensi partisipasi 26 responden (22,03%). Intensitas partisipasi tertinggi pada kampung Kentekstar (60,00%), diikuti Tanah Merah Indah (36,36%), Ipingoisi (31,11%), dan Soribo (28,57%) dengan frekuensi 41 responden (34,75%). Tingkat partisipasi masyarakat masuk dalam kategori “sangat tidak aktif dengan indek partisipasi berada pada rentang 1 – 25. ABSTRACTParticipation of community in the management is fundamental that determines the success of the programs. In the perspective of natural resources conservation, participation is a basic principle that determines the success of achieving the programs. The purpose of research is to determine the function, the intensity and the level of community participation in Wosi Rendani protected forest management program. The results of the research that participation indexs in the management of protected forest of Wosi Rendani based functions at Kentekstar village highest participation (60.0%) followed Ipingoisi (31.11%), Soribo (28.57%) and lowest in Tanah Merah Indah (27.27%) with the value of the frequency of participation of 41 respondents (34.75%). Overall all respondents would participate in the function of the distribution with participation frequency of 26 respondents (22.03%). Intensity of participation at Kentekstar village is highest (60.0%) followed Tanah Merah Indah (36.36%), Ipingoisi (31.11%) and lowest in the Soribo (28.57%) with the value of the frequency of participation of 41 respondents (34.75%). The level of community participation in the category of "very active with Participation Index values were in the range 1 – 25.